In situ synthesis of amorphous titanium dioxide supported RuO2 as a carbon-free cathode for non-aqueous Li–O2 batteries. Issue 94 (26th September 2016) - Kim, Jisu; Kim, Yeon; Wu, Mihye; Yoon, Dae-Ho; Kang, Yongku; Jung, Ha-Kyun
Abstract : Amorphous TiO2 supported crystalline RuO2 (a-TiO2 /c-RuO2 hybrid) enhanced battery performance, and this enhancement was attributed to the crystallinity of the TiO2 that amorphous TiO2 is more electrochemically active toward ORR/OER than crystalline TiO2 . Abstract : Amorphous TiO2 supported crystalline RuO2 (a-TiO2 /c-RuO2 hybrid) was prepared as a carbon-free cathode by in situ sol–gel synthesis, and its electrochemical performance in non-aqueous Li–O2 batteries was investigated for the first time. The a-TiO2 /c-RuO2 hybrid enhanced battery performance, and this enhancement was attributed to the crystallinity of the TiO2 . It was found that amorphous TiO2 is more electrochemically active toward the discharge/charge processes than crystalline TiO2 . The a-TiO2 /c-RuO2 hybrid exhibited good reversibility as well as cyclic stability, making it a promising carbon-free cathode material for non-aqueous Li–O2 batteries.